Phyllodes Tumors of the Breast: An Analysis of 53 Cases From a Single Institution. (21st September 2018) - Umar, Beena; Robison, Ariane; Chitale, Dhananjay
Abstract: Mammary phyllodes tumors (PT) are rare tumors with diverse biologic behavior. They are classified into benign, borderline, and malignant categories on the basis of a constellation of histological parameters. Benign phyllodes tumors share overlapping morphologic features with cellular fibroadenoma, whereas, on the other end of the spectrum, separation of the malignant phyllodes tumor from metaplastic carcinoma and primary breast sarcoma can be challenging. With this background, our aim of the study was to review clinicopathologic features of this rare mammary neoplasm in our large metropolitan health care system over a period of 12 years. An electronic database search in the anatomic pathology laboratory information system for all cases diagnosed as fibroepithelial tumors or phyllodes tumor in female breast was performed from 2005 to 2016. Cases were retrospectively reviewed, and the following data elements were recorded: age, primary diagnosis, size, margin status, and pertinent histologic features to differentiate morphologic subtypes (stromal overgrowth, cellularity, mitoses, necrosis, nuclear atypia, infiltrative vs pushing borders). There were 53 cases of PT that fit the criteria for this study. The mean age was 48 years (range, 17 to 86 years). Histologically, 28 (53%) cases were classified as benign (5 tumors with mixed fibroadenoma and phyllodes tumor morphology), 16 (30%) borderline, and 9 (17%) malignant phyllodes tumors. The mean tumor size was 4.9 cm (1 to 20 cm). Five of 53 (9.4%) tumors recurred (3/53 benign, 1/53 borderline, 1/53 malignant). One patient with malignant PT in our series developed distant metastasis to pleura and died of the disease. PTs are rare tumors that occur in relatively young women, when compared with invasive carcinoma of the breast. They may reach a large size in the absence of nodal or distant metastases. Our study findings are consistent with other published studies but in addition further highlight unpredictable biologic behavior.